Rational institutions yield hysteresis - Rafael DiTella; Robert MacCulloch (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
We argue that labor market institutions are endogenous. Our analysis focuses on the government's decision to set unemployment benefits in response to an unemployment shock in a simple, reduced-form model of the labor market. It is found that the largest increases in benefits should occur in economies where the adverse incentive effects of benefits are largest. Adjustment costs of changing benefits can introduce hysteresis in benefit setting and unemployment. Both (very) bad and good temporary shocks (including monetary) can permanently reduce unemployment benefits and the unemployment rate. A desirable feature of the model is that the mechanism yielding hysteresis (which requires a concave utility function) ceases to operate when unemployment tends to one.
Keywords: J6; 330; Optimal unemployment benefits; hysteresis; natural rate of unemployment; Arbeitslosigkeit; Arbeitslosenversicherung; Hysteresis; Optimale Besteuerung; Schock; Anpassungskosten